Roald Dahl: the magic finger - Corrall, R. J. (Ladybird Books London, 2020)
"I have a Magic Finger. When I get angry ... things begin to happen!" What will happen when the finger is pointed at the Gregg family? Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language